Genetic diversity in Stylosanthes species : a GIS mapping approach - Jones, Peter G.; Rebgetz, R; Maass, Brigitte L.; Kerridge, Peter C. (International Center for Tropical Agriculture, 1996)
We describe a method of fitting a model of germplasm distribution to climate data and illustrate it`s use in mapping the continental distribution of five Stylosanthes species. The climate data used are the monthly totals of rainfall and the monthly mean temperatures and diurnal temperature ranges. The data are rotated in time to standardize dates and then used in a principal components analysis to develop a function giving the probability density of a climate being similar to those of a calibration set of germplasm accessions. We present maps of the distributions of the calibration sets and probability densities and show how they can be used to guide further collection and to develop hypotheses of the genetic diversity within and between species